Milenial Generations’ Interest Of Buying As A Quality Impact Of Silverqueen Chocolate Products In Bandung City - Handayani, Rini (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Millennials like chocolate, 55% admit to giving gifts of chocolate compared to other products. Silverqueen chocolate occupies the top position in chocolate bars, but has not been able to encourage consumer buying interest. The purpose of this study was to determine how product quality, consumer purchase interest, and its effects. The research method used is descriptive and verification. Data collection techniques using questionnaires, interviews, and observations. The sample in this study were millennial consumers who like Silverqueen chocolate in the city of Bandung. The minimum sample in this study was 130 respondents, and the analysis tool used was simple regression. The results showed that the quality of Silverqueen products and the buying interest of millennial’ consumers was quite good.